THE INFLUENCE OF SCHOENSTATT'S PEDAGOGY ON TEACHING PRACTICE IN THE 21ST CENTURY - Lopes Monteiro de Souza, Gislaine; de Araújo Azevedo, Jacy (Revista Gênero e Interdisciplinaridade, 2021)
This research aimed to present the Schoenstatt pedagogy that was organized by Father José Kentenich in Germany in the 20th century, making an analysis of how Father Kentenich's conceptions can help teachers in their teaching practice today. Schoenstatt's pedagogy has as its essence the transformation of man, awakening in him a free identity, determined and capable of acting in society with his potential in an integrated, authentic and dynamic way, exercising his social, moral and spiritual responsibilities. The methodology used is based on bibliographical research that presents a synthesis of the emergence of Schoenstatt pedagogy. The article is organized into sections. In the first section we will deal with the biography of Father José Kentenich and the emergence of Schoenstatt pedagogy. In the second section, we will report on their philosophical and pedagogical conceptions, making a parallel with the pedagogical trends of Libâneo. In the third section we highlight some places where this pedagogy is currently applied.